The role of carbon metrics in supporting built-environment professionals - Thomas Lützkendorf (Buildings & Cities, 2020)
Highlights Protecting the climate is an indispensable contribution to the conservation of the ecosystem. One approach is to reduce greenhouse gas (GHG) emissions to be within planetary boundaries. The quantification, allocation, assessment and control of GHG emissions affect a variety of actors, for example, manufacturers, planners, designers, clients, investors, contractors, facility managers, policy-makers, regulators, environmental economists, etc. To be effective, these actors need indicators to measure and influence GHG emissions associated with the creation and operation of the built environment. This editorial introduces the special issue and considers the creation and use of a coherent set of carbon metrics across different scales: construction products, buildings, neighbourhoods, cities as well as building stocks. Of particular importance is the agreement of clear terms, definitions, system boundaries and calculation procedures. Questions about scalability and aggregation are addressed as well as methodological issues associated with the use of biomass, a fair approach to budget-sharing and the design of emission balances including compensation options (e.g. offsetting and sequestration). Complementing the carbon metric approach is the development of a scalable carbon budget to determine the allocation of GHGs to a specific context: building, neighbourhood, city or building stock.